1995
DOI: 10.1007/bf01404846
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of elevation of urine catecholamines in intracerebral haemorrhage

Abstract: Autonomic nervous system dysfunction is a common complication of severe intracranial disease. The aim of this study was to reveal the autonomic changes in patients suffering from acute intracerebral haemorrhage (ICH). 25 patients with spontaneous ICH within 24 hours of onset of symptoms were included. All patients were treated with standardised medical management and the meta- and normetanephrines were detected by high performance liquid chromatography (HPLC) in 24-hour urine every day. The mean level of norme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
(5 reference statements)
1
8
1
Order By: Relevance
“…In the present case, the morning plasma catecholamine and urinary normetanephrine levels were elevated on days 2 and day 7, respectively, and remained within two-fold of the upper limit of normal, although the urinary normetanephrine value normalized on day 12. These findings are significant and may have affected the ARR, although they were relatively mild compared with those of previous reports (15,16,18).…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…In the present case, the morning plasma catecholamine and urinary normetanephrine levels were elevated on days 2 and day 7, respectively, and remained within two-fold of the upper limit of normal, although the urinary normetanephrine value normalized on day 12. These findings are significant and may have affected the ARR, although they were relatively mild compared with those of previous reports (15,16,18).…”
Section: Discussioncontrasting
confidence: 51%
“…In that case, the plasma norepinephrine and urinary metanephrine levels were elevated to approximately five times above the upper limit of normal at presentation and normalized on day 23. In the acute phase of intracranial hemorrhage, sympathetic nerve activation occurs secondary to an elevated intracranial pressure (16), which stimulates renin secretion (17). Leow et al (18) reported an excessive amount of catecholamines and metanephrine triggered by sympathetic dysautonomia in the setting of acute intracranial hemorrhage, describing this phenomena as "biochemically pseudopheochromocytoma," as the plasma catecholamine and urinary metabolite levels mimic the endocrinological laboratory findings of pheochromocytoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Autonomic changes also underlie the poststroke immunodepression syndrome with increased susceptibility to infection after ICH [10]. Indeed, several studies confirmed negative outcome effects of autonomic impairment after intracerebral or subarachnoid hemorrhage [1,32,33]. Interestingly, we found that both IVH score and BRS were associated with admission hyperglycemia, blood pressure elevations, and leukocytosis at admission.…”
Section: Discussionsupporting
confidence: 49%